2017
DOI: 10.4265/bio.22.229
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Surfactants in the Laundry Detergents and Isolation of the Surfactant Resistant Aquatic Bacteria

Abstract: Linear alkylbenzene sulfonate LAS and polyoxyethylene lauryl ether POLE are major surfactants contained in the laundry detergents. In the present study, the antibacterial activities of the surfactants to aquatic microorganisms were compared. When freshwater samples from a small river in Okayama city were treated with each of the surfactants, only LAS showed the significant antibacterial activity. Several strains, which survived after the treatment with 2.0% LAS, were isolated and identified by sequencing of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…These results indicate that both surfactants have significant bactericidal activities against soil bacteria, but the bactericidal activity of LAS is much higher than POLE. Similarly, Maehara and Miyoshi (2017) previously reported that only LAS showed sufficient bactericidal action against aquatic bacteria.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…These results indicate that both surfactants have significant bactericidal activities against soil bacteria, but the bactericidal activity of LAS is much higher than POLE. Similarly, Maehara and Miyoshi (2017) previously reported that only LAS showed sufficient bactericidal action against aquatic bacteria.…”
mentioning
confidence: 69%
“…Linear alkylbenzene sulfonate (LAS), an anionic surfactant, and polyoxyethylene lauryl ether (POLE), a non‐ionic surfactant, are the major active ingredients contained in various washing detergents. We recently reported that when freshwater samples from a small river were treated with 0.02%–2.0% of each surfactant, only LAS showed significant antibacterial activity against aquatic bacteria (Maehara & Miyoshi, 2017). However, in that study, we found that several Enterobacteriaceae strains could survive even after treatment with 2.0% LAS, which was about 10–20 times the standard working concentration.…”
Section: Surfactant Soil Sample Plate Colonies Formeda Survival Rate...mentioning
confidence: 99%
See 2 more Smart Citations
“…40 Linear alkyl benzene sulphonic acid also reported to have antibacterial activity against some aquatic bacteria. 41 Therefore, it is not surprising that ABSAtreated fabric showed good antibacterial activity. ABSA polymer probably induced changes in the pH in and also caused hyperpolarisation of the cell membrane of bacteria resulting in the death of bacteria.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%